ECCE Principals' Strategy to Improve Teacher Competence in Implementing the Independent Curriculum - Aisah, Imas; Nurhayati, Sri; Rukanda, Nandang (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
This study aims to investigate the strategies used by Early Childhood Care and Education (ECCE) principals in Kecamatan Arcamanik, Bandung, to enhance teacher competence for the Independent Curriculum. Utilizing a qualitative approach with case study method, observation and semi-structured interviews were conducted with principals from 10 ECCE institutions, supplemented by the review of relevant documents and institutional records. The data were analyzed thematically, drawing upon current educational research to contextualize the findings within broader educational theory and practice. The findings reveal a diverse range of strategies employed by the principals, including the provision of educational resources, ongoing professional development, collaborative learning, and the utilization of support services and platforms. These strategies vary in their alignment with current educational research, reflecting the unique context of each institution. The study highlights the importance of tailoring teacher development strategies to meet the specific needs and resources available to educational institutions. Implications of this study are significant for both policymakers and practitioners, particularly in Indonesia and similar contexts.